Exenatide once-weekly improves metabolic parameters, endothelial dysfunction and carotid intima-media thickness in patients with type-2 diabetes: An 8-month prospective study. (March 2019) - Patti, Angelo Maria; Nikolic, Dragana; Magan-Fernandez, Antonio; Giglio, Rosaria Vincenza; Castellino, Giuseppa; Chianetta, Roberta; Citarrella, Roberto; Corrado, Egle; Provenzano, Francesca; Provenzano, Vincenzo; Montalto, Giuseppe; Rizvi, Ali A.; et al.
Highlights: Treatment with exenatide showed cardiovascular safety. An improvement on atherosclerosis surrogate markers was found. The changes were independent of glucometabolic control. Abstract: Aim: To evaluate the effect of exenatide long acting release (LAR) on carotid intima-media thickness (IMT) and endothelial function in patients with type 2 diabetes mellitus. Methods: Sixty subjects with type 2 diabetes mellitus were treated with exenatide LAR as add-on to stable doses of metformin for 8 months in an open label study. Anthropometric variables, lipid profile and glycemic parameters were assessed by routine analysis. Carotid IMT by Doppler ultrasound and endothelial function by flow-mediated dilation of the brachial artery were also assessed. Results: Exenatide significantly improved fasting glycaemia (from 8.8 ± 2.8 to 7.3 ± 2.2 mmol/L, p < 0.0001), HbA1c (from 8.0 ± 0.4 to 6.9 ± 1.1%, p < 0.0001), body mass index (from 33 ± 9 to 31 ± 6 kg/m 2, p = 0.0348) and waist circumference (from 109 ± 13 to 106 ± 13 cm, p = 0.0105). There was a significant improvement of the lipid profile, except in triglyceride level where no changes were observed. Carotid IMT and flow-mediated dilation were also improved (from 0.98 ± 0.14 to 0.87 ± 0.15 mm and from 5.8 ± 1.3 to 6.8 ± 1.7%, respectively; p < 0.0001 for both). Conclusions: Treatment with exenatide LAR led to improved cardio-metabolic parameters, including carotid IMT and flow-mediated dilation, independently of glucometabolic control. These results may help to explain, at least in part, the cardiovascular safety of exenatide LAR, as recently reported in cardiovascular outcome trials.